Odpowiedzi

Najlepsza Odpowiedź!
2010-03-25T11:23:12+01:00
Wyłącz wspólny czynnik przed nawias .
a) -8x + 6y - 2 =2(-4x + 3y - 1)
b) 6a - 12b + 18c =6(a - 2b + 3c)
c) 21x² + 14y³ - 7 =7(3x² + 2y³ - 1)
d) - 1,6a - 0,8b- 4,8c =- 0,8(2a + b+ 6c)
4 4 4
2010-03-25T11:23:26+01:00
A) -8x + 6y - 2 =2(-4x+3y-1)
b) 6a - 12b + 18c =6(a-2b+3c)
c) 21x² + 14y³ - 7 =7(3x²+2y³ -1)
d) - 1,6a - 0,8b- 4,8c =0,8(-2a-b-6c)
1 4 1
2010-03-25T11:44:47+01:00
A) -8x+6y-2 =2(-4x+3y-1)
b) 6a-12b+18c = 6(a-2b+3c)
c) 21x²+14y³-7 = 7(3x²+2y³-1)
d) -1,6a-0,8b-4,8c = -0,8(2a+b+6c)
2 5 2